Electrocatalytic mechanism for overall water splitting to produce sustainable hydrogen by 2D Janus MoSH monolayer - Deobrat Singh; Nisha Singh; Yogesh Sonvane (npj 2D Materials and Applications)
Abstract In the present work, we investigates the potential of two dimensional (2D) Janus MoSH monolayer as an electrocatalyst for overall water splitting using first-principles calculations. Our results shows that 2D Janus MoSH monolayer exhibits excellent structural stability and electronic properties, which are essential for efficient electrocatalysis. We find that the charge transfer mechanism between Mo and S atoms plays a crucial role in the electrocatalytic activity of 2D Janus MoSH monolayer. Due to the asymmetric structure of MoSH monolayer, it has intrinsic electric field with dipole moment of 0.24 D. Moreover, we demonstrate that 2D Janus MoSH monolayer exhibits high catalytic activity for both hydrogen evolution reaction (HER) with overpotential 0.04 V and oxygen evolution reaction (OER) with overpotential 0.11 V, making it a promising candidate for overall water splitting. Our findings have significant implications for the design and optimization of 2D monolayered materials for renewable energy production. By providing insights into the underlying mechanisms of HER and OER on 2D Janus MoSH monolayer, our study paves the way for the development of efficient and sustainable electrocatalysts for water splitting. We hope that current work will be helpful in understanding the electrocatalytic mechanism of 2D Janus MoSH monolayer and its potential applications in renewable energy production.